Pendampingan Pembuatan Soal Ujian Kredibel bagi Guru Madrasah di Kabupaten Soppeng - Rukli Rukli; Munirah Munirah (Universitas Negeri Makassar, 2018)
The purpose of this activity is how to empower teachers to make credible questions through mentoringmethod. The results of the identification of the problem in making credible questions at Islamic boarding school inSoppeng shows that this mentoring is needed for the teachers to increase their knowledge in understanding crediblequestions through, to improve their skills in making questions based on the indicators, and to improve their skills inanalysing questions qualitatively. The result of this mentoring showed that the implementation of this mentoring wasat Madrasah Tsanawiah Yasrib Islamic Boarding School in Watansoppeng, South Sulawesi. It is one of favouriteschools in Soppeng for elementary graduates. The questions used by teachers have not been arranged well wheremost of the questions are categorized as very bad and do not reflect the activities of productive students. Thismentoring helps them to make good questions, considering the questions theory, good indicators, especially themain problem (stem), and the competency in analysing the problems qualitatively. Long-term planning of mentoringactivities where the teachers have their own standard questions for school exams and other exams. Generally,teachers make 20 sample questions for each subject to be developed further as an incubator question and questionbank with good criteria.